Exploring the processes of emergent leadership in a netball team: Providing empirical evidence through discourse analysis. Issue 1 (February 2021) - Schnurr, Stephanie; File, Kieran; Clayton, Daniel; Wolfers, Solvejg; Stavridou, Anastasia
In line with recent developments in leadership research which conceptualise leadership as a discursive and collaborative process rather than a set of static attributes and characteristics displayed by individuals, this paper explores some of the discursive processes through which leadership emerges in a sports team. Drawing on over ten hours of naturally occurring interactions among the players of a women's netball team in the UK, and applying the concepts of deontic and epistemic status and stance, we identify and describe some of the specific processes through which leadership is claimed and assigned, as well as rejected, passed on, and eventually accepted by different team members at different points throughout an interaction. While the processes outlined in our analysis contribute to theoretical discussions regarding the notion of emergent leadership, this paper also demonstrates the benefits of taking a discourse analytical approach to leadership, and outlines how such an approach enables researchers to empirically capture emergent leadership in situ.